Pastoral Development in Ethiopia : Trends and the Way Forward - Gebremeskel, Esayas Nigatu (Washington, DC: World Bank, 2019)
Despite half a century of development efforts, multidimensional deprivation and vulnerability to shocks remain a serious problem in Ethiopia’s pastoral areas. A review of past and ongoing pastoral and agro-pastoral (PAP) development efforts in Ethiopia, analysis of the current socioeconomic situation in relation to PAPs, and an extensive literature review of emerging knowledge on the topic point to the need for future PAP development to focus on resilience, transformation, and sustainability. This study, which was commissioned by the World Bank and the International Fund for Agricultural Development (IFAD), proposes six strategic pillars: livelihood support for improved pastoral and agro-pastoral production; livelihood diversification and improved agro-pastoral extension; integrated rangeland and water development, and secure access to key resources; transformation and commercialization of the livestock industry; enhanced access and use of basic social and economic services; enhanced social protection and disaster risk management; and institutional and human capacity development. In addition, intervention-planning needs to be sensitive to conflict, should mainstream gender issues and nutrition, and should emphasize women and youth employment, climate change and adaptation, information technology, action-oriented research, and knowledge management and documentation.